Upregulation of cell cycle genes in head and neck cancer patients may be antagonized by erufosine's down regulation of cell cycle processes in OSCC cells - Ansari, Shariq S.; Sharma, Ashwini Kumar; Bergmann, Frank (OncoTarget, 2018)
The TCGA database was analyzed to identify deregulation of cell cycle genes across 24 cancer types and ensuing effects on patient survival. Pan-cancer analysis showed that head and neck squamous cell carcinoma (HNSCC) ranks amongst the top four cancers showing deregulated cell cycle genes. Also, the median gene expression of all CDKs and cyclins in HNSCC patient samples was higher than that of the global gene expression. This was verified by IHC staining of CCND1 from HNSCC patients. When evaluating the quartiles with highest and lowest expression, increased CCND1/CDK6 levels had negative implication on patient survival. In search for a drug, which may antagonize this tumor profile, the potential of the alkylphosphocholine erufosine was evaluated against cell lines of the HNSCC subtype, oral squamous cell carcinoma (OSCC) using in-vitro and in-vivo assays. Erufosine inhibited growth of OSCC cell lines concentration dependently. Initial microarray findings revealed that cyclins and CDKs were down-regulated concentration dependently upon exposure to erufosine and participated in negative enrichment of cell cycle processes. These findings, indicating a pan-cdk/cyclin inhibition by erufosine, were verified at both, mRNA and protein levels. Erufosine caused a G2/M block and inhibition of colony formation. Significant tumor growth retardation was seen upon treatment with erufosine in a xenograft model. For the decreased cyclin D1 and CDK 4/6 levels found in tumor tissue, these proteins can serve as biomarker for erufosine intervention. The findings demonstrate the potential of erufosine as cell cycle inhibitor in HNSCC treatment, alone or in combination with current therapeutic agents.
Published: December 20, 2017
Gesehen am 19.06.2018